HISTORICAL FOUNDATIONS OF MUHAMMADIYAH: ISLAMIC REFORM, EDUCATIONAL MODERNIZATION, AND SOCIAL TRANSFORMATION IN INDONESIA - Siregar, Ahsari Fadli; Hayat, Muhammad (International Journal of Multidisciplinary Reseach, 2026)
Muhammadiyah represents one of the most influential Islamic reform movements in Indonesia, playing a pivotal role in reshaping religious thought, education, and social engagement since the early twentieth century. This article examines the historical foundations of Muhammadiyah by analyzing the socio-religious context prior to its establishment, the intellectual formation of its founder K.H. Ahmad Dahlan, and the core ideological principles underpinning the movement. Employing qualitative historical analysis based on literature review, this study reveals that Muhammadiyah emerged as an integrated response to colonial educational marginalization, religious syncretism, and social inequality. The findings demonstrate that Muhammadiyah’s reformist paradigm-grounded in tajdīd, educational modernization, and organized social action-remains relevant in addressing contemporary challenges.